The process for implementing the case-method teaching approach - ĐOÀN TRIỆU LONG (Political Theory Journal, 2026)
The case-method teaching approach aims to motivate and promote critical thinking and to develop learners’ capacity to solve real-world problems. This learner-centered method focuses on developing learners’ competencies. This article systematizes the procedures for applying the case-method approach, clarifies its role and significance, outlines the specific steps to carry it out, and highlights important considerations during implementation. Through this, it seeks to provide practical reference material for instructors at academies and political schools and for other training and professional-development institutions engaged in pedagogical innovation.